أساليب الشراكة بين القطاعين العام و الخاص في إطار إنجاز المشاريع العمومية - كريمة, شايب باشا (Université de M'sila, 2020)
حظي موضوع الشراكة بين القطاعين العام والخاص باهتمام كبير على مستوى الحكومات لما يلعبه من دور في تشييد و تمويل البني التحتية. خاصة أمام تزايد الإنفاق العام في الدول النامية،والذي يقابله عجز في الموازنة العامة.وعليه فإن الأمر يتطلب جمع كل الإمكانيات من موارد مالية وخبرات تقنية وتكنولوجيا لكل القطاعين العام و الخاص للتشارك من أجل إنشاء وتشغيل خاصة تلك المشاريع الاستراتيجية .وتشير تجارب البلدان المختلفة إلى أن مشاريع البنية التحتية هي المرشحة في العادة للشراكة بين القطاعين العام والخاص لتغطية الاحتياجات المتزايدة لهذا النوع من المشاريع والمرافق. فما دور هذه العقود في إقامة منشآت قاعدية ومدى انعكاس ذلك في الجزائر ؟. Public-Private Partnership (PPP) has received considerable attention at the government level for its role in the construction and financing of infrastructure. Especially in light of the increase in public spending in developing countries, which is offset by a deficit in the public budget. Therefore, it requires the collection of all possibilities of financial resources and technical expertise and technology for both the public and private sectors to participate in the establishment and operation of these special strategic projects. Infrastructure projects are usually nominated for public-private partnership to meet the growing needs of these types of projects and facilities. What is the role of these contracts in the establishment of grassroots facilities and the extent of the reflection in Algeria?
Keywords: الشراكة-القطاع العام –القطاع الخاص-البناء والتشغيل-نقل الملكية.